Thermal and exhumation history of the central Rwenzori Mountains, Western Rift of the East African Rift System, Uganda - Bauer, Friederike Ursula; Glasmacher, Ulrich A.; Ring, Uwe; Schumann, A.; Nagudi, B. (International journal of earth sciences, 2010)
The Rwenzori Mountains (Mtns) in west Uganda are the highest rift mountains on Earth and rise to more than 5,000 m. We apply low-temperature thermochronology (apatite fission-track (AFT) and apatite (U-Th-Sm)/He (AHe) analysis) for tracking the cooling history of the Rwenzori Mtns. Samples from the central and northern Rwenzoris reveal AFT ages between 195.0 (±8.4) Ma and 85.3 (±5.3) Ma, and AHe ages between 210.0 (±6.0) Ma to 24.9 (±0.5) Ma. Modelled time-temperature paths reflect a protracted cooling history with accelerated cooling in Permo-Triassic and Jurassic times, followed by a long period of constant and slow cooling, than succeeded by a renewed accelerated cooling in the Neogene. During the last 10 Ma, differentiated erosion and surface uplift affected the Rwenzori Mtns, with more pronounced uplift along the western flank. The final rock uplift of the Rwenzori Mtns that partly led to the formation of the recent topography must have been fast and in the near past (Pliocene to Pleistocene). Erosion could not compensate for the latest rock uplift, resulting in Oligocene to Miocene AHe ages.
Gesehen am 07.12.2022